2018
DOI: 10.1186/s13578-018-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and CaSR/IP3R in prostate cancer development

Abstract: Prostate cancer (PrCa) progression and mortality are associated with calcium metabolism, parathyroid hormone level, and vitamin D level. However, the lack of comprehensive understanding on the molecular rationale of calcium intake, serum homeostasis, and cytoplasmic function, is critically hindering our ability to propose a mechanism based technique for targeting calcium in PrCa. Recently, studies performed on PrCa samples have shown that calcium-sensing receptor regulates cytoplasmic calcium levels in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Pharmacological evidence demonstrated that the attendance of IP3 and ryanodine receptor channels signaling as calcium-induced calcium release are responsible for this calcium homeostasis, because these derivatives with infrequent peroxide bridge have several P-type Ca 2+ ATPases involved in the ER-type reuptake mechanism at the proposed target sites 70 . Recently, research into extracellular Ca 2+ linking to the trichocysts associated with fastest dense core-secretory vesicle exocytosis has elucidated that calcium homeostasis is critical in many physiological and pathological processes including protein secretion, motility, cell invasion, and differentiation 51 , 75 . With the involvement of putative mitochondrial Ca(2+)/H(+) exchanger, IP3/cADPR-mediated endoreticular calcium release via RyRs, and parasites-only CDPKs, our suggestion of a combination of different compounds from diverse calcium signaling pathways, such as a cocktail of BKI plus artemisinin, is worthy of more intensive studies.…”
Section: Essential Cdpks As Potential Drug Targets Against the Malarimentioning
confidence: 99%
“…Pharmacological evidence demonstrated that the attendance of IP3 and ryanodine receptor channels signaling as calcium-induced calcium release are responsible for this calcium homeostasis, because these derivatives with infrequent peroxide bridge have several P-type Ca 2+ ATPases involved in the ER-type reuptake mechanism at the proposed target sites 70 . Recently, research into extracellular Ca 2+ linking to the trichocysts associated with fastest dense core-secretory vesicle exocytosis has elucidated that calcium homeostasis is critical in many physiological and pathological processes including protein secretion, motility, cell invasion, and differentiation 51 , 75 . With the involvement of putative mitochondrial Ca(2+)/H(+) exchanger, IP3/cADPR-mediated endoreticular calcium release via RyRs, and parasites-only CDPKs, our suggestion of a combination of different compounds from diverse calcium signaling pathways, such as a cocktail of BKI plus artemisinin, is worthy of more intensive studies.…”
Section: Essential Cdpks As Potential Drug Targets Against the Malarimentioning
confidence: 99%
“…IP 3 R are modulated in response to androgen deprivation in LnCAP cells [10]. Additionally, an analysis of the TCGA database revels that IP 3 R is altered in 30% of prostate tumors [11]. Together this information indicates that PMCA and IP 3 R are good targets for treating advanced, androgen-independent prostate cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that inositol 1,4,5-trisphosphate receptor (IP3R), a calcium ion channel, is correlated with invasive behavior and progression of several types of neoplasia including breast cancer, prostate cancer, uterine cancer, ovarian cancer, and pulmonary adenocarcinoma [9][10][11][12]. Its expression is also associated with poor prognosis in colorectal carcinoma [13].…”
Section: Introductionmentioning
confidence: 99%